The impact of innovative behaviors on academic misconduct among graduate students: a mediated moderation model - Su, Peng; He, Mu (Frontiers in Psychology, 2023)
Academic misconduct among graduate students presents a challenging issue within graduate education. This study aims to investigate the impact of innovative behavior on graduate student academic misconduct while analyzing the mediating role of academic anxiety and the moderating effects of educational level and employment confidence. The participants in this study were 677 graduate students from universities in Beijing. The research findings indicate that graduate student innovative behavior negatively predicts academic misconduct, with a more prominent display of innovative behavior associated with a lower likelihood of academic misconduct. Academic anxiety plays an intermediary role between graduate student innovative behavior and academic misconduct. Educational level and employment confidence respectively serve as moderators in the latter part of the mediation effects of graduate student innovative behavior, academic anxiety, and academic misconduct.Therefore, to enhance graduate students' innovative capabilities, it is essential to emphasize their innovative behavior, alleviate negative emotions like academic anxiety, and pay special attention to graduate students with lower educational levels and lower employment confidence in order to reduce instances of academic misconduct.